2013
DOI: 10.1021/jp405312a
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Influence on Phospholipid Films Investigated with Single Molecule Fluorescence Measurements

Abstract: Single molecule fluorescence measurements are used to probe the effects of GM1 in DPPC monolayers. Langmuir-Blodgett films of GM1 and DPPC were doped with ~10−8 mol% of the fluorescent lipid probe, BODIPY-PC, and transferred onto glass substrates at 23 mN/m. As shown previously, the individual orientation of each BODIPY-PC probe in the membrane can be measured using defocused polarized total internal reflection fluorescence microscopy, revealing changes in film properties at the molecular level. Here, BODIPY-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Moreover, the steric hindrance of neighboring GM1 headgroups favors the interstitial placement of DPPC molecules. The observed mixture of phospholipids and gangliosides in clusters is supported by experimental studies that unveiled a maximum lipid tail order for a GM1/DPPC ratio of ∼1:3. , …”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Moreover, the steric hindrance of neighboring GM1 headgroups favors the interstitial placement of DPPC molecules. The observed mixture of phospholipids and gangliosides in clusters is supported by experimental studies that unveiled a maximum lipid tail order for a GM1/DPPC ratio of ∼1:3. , …”
Section: Resultsmentioning
confidence: 52%
“…Furthermore, single-molecule fluorescence measurements using BODIPY-PC have shown that concentrations below 5 mol % GM1 as well as high concentrations of more than 20 mol % GM1 induce disorder in DPPC membranes. In turn, the order of BODIPY-PCs is highest at 15–20 mol % GM1 . Apart from these experimental studies, an atomistic molecular dynamics simulation study of a single GM1 molecule revealed an induced local disorder in the arrangement of the surrounding chains and headgroups because the sphingosine chain of GM1 folds up and becomes stacked beneath the sugar residues lying on the surface .…”
Section: Introductionmentioning
confidence: 98%
“…We have previously used singlemolecule orientation measurements to characterize the evolution in lipid monolayers with surface pressure, 32−34 relative humidity, 37 and the presence of additives such as GM1 and cholesterol. 35,36 Here we extend those studies to compare the tilt angle of BODIPY-cholesterol doped into DPPC/DOPC/Chol and SM/DOPC/Chol monolayers as a function of cholesterol. Figure 5 shows a representative defocused single-molecule fluorescence image of BODIPY-cholesterol doped into a DPPC/DOPC monolayer at ∼10 −8 mol %.…”
Section: ■ Results and Discussionmentioning
confidence: 72%
“…The DNA-intercalating fluorophores YOYO-1 [34] and SYTOX Orange [35] adopt fairly rigid angles perpendicular to the DNA axis and have been used for single-molecule studies of DNA orientation within cells. In addition, the membrane-binding DiI has been used at single-molecule sensitivity to detect membrane packing [36], and effects of gangliosides on the formation of lipid rafts [37]. …”
Section: Choice Of Probesmentioning
confidence: 99%
“…Defocused imaging has been applied to a number of biological systems, including the orientation tracking of bifunctional rhodamine attached to calmodulin on myosin V [97], observation of endocytosed vesicles within living cells [111], estimation of the torque produced during the 360° rotations of F 1 -ATP synthase [113], recording the orientation of carbohydrate- binding modules on cellulose microfibrils [116], determination of lipid orientation during membrane packing [36, 117] and raft formation [37]. …”
Section: Emission Pattern Imagingmentioning
confidence: 99%